Mobile Learning Innovation: Android-Based Smart Informax Development to Optimize Practicing Vocational School Students in Industry - Said Thaha Ghafara; Ari Syaiful Rahman Arifin; Muhammad Giatman; Fadhilah (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2026)
The application of innovative technology in learning can enhance the competence of students, which corresponds to the needs of the world of work and industry. The aim of this study is to create an Android-based learning media—also known as a smart informax realised in an application that can be accessed using a smartphone. This application supports project-based learning even if students are in the process of internship in industry. It can be used anywhere, in school, out of school or for students in fieldwork practice (PKL). This application is designed to suit the needs of students in the world of work and industry. The development of this application uses R&D methods adapted to the ADDIE development model. There are five stages of development: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. This study involved 30 students of grade X majoring in computer network engineering at SMKN 1 Tanjungpinang as research participants. This study used observation and questionnaires as data collection techniques. The descriptive data collection method used by materialists and media experts is the Likert scale, which has four options of answers. The material expert evaluation results obtained a total score of 98.00 with an average score of 3.62 out of 27 evaluation indicators with a percentage of 90.74%, so it belongs to the category 'very suitable for use'. With a positive student response with an average of 92.67% at the media implementation stage, this falls into a highly qualified category. Evaluation results of application use by students showed an average improvement of about 43.74% in student learning outcomes. This smart Informax application is specially designed to support project-based learning to improve student competence and student skills in industry-based projects that will affect student performance during their internship in the world of industry.